PEMODELAN ARSITEKTUR SISTEM INFORMASI PRESENSI UNIVERSITAS PRIMAKARA MENGGUNAKAN UNIFIED MODELING LANGUAGE DENGAN METODE SCRUM - Yuliani, Ni Kadek; Paramitha, A.A. Istri Ita; Suyasa, I Putu Buda (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
In the digital era, information technology development is essential for various institutions, including universities. As educational institutions, universities require efficient systems to support administrative activities, such as attendance management. This research focuses on designing an employee attendance information system for Primakara University using the Scrum method and Unified Modeling Language (UML). Scrum was chosen for its adaptive and iterative approach, enabling development through sprints with regular evaluations. UML served as a visual modeling tool to systematically structure system elements, including use case diagrams, activity diagrams, sequence diagrams, and database structures. The Scrum method was implemented over four months with 8 sprints, conducting two weekly meetings to ensure iterative progress. The research resulted in one use case diagram, 16 activity and sequence diagrams, as well as Entity-Relationship Diagrams (ERD) and physical data models. These outputs provide a structured overview of system flow and data architecture. This approach facilitates effective communication between the development team and stakeholders while delivering a comprehensive system design. The application of Scrum and UML in this study demonstrates a practical framework for building efficient, systematic, and adaptable attendance management systems, meeting the needs of modern educational institutions.